Development of moral disengagement and self-regulatory efficacy assessments relevant to doping in sport and exercise. (May 2018) - Boardley, Ian D.; Smith, Alan L.; Mills, John; Grix, Jonathan; Wynne, Ceri; Wilkins, Luke
Abstract: Objectives: To develop Moral Disengagement (MD) and Self-Regulatory Efficacy (SRE) instruments relevant to doping in sport and exercise and provide evidence for the validity and reliability of instrument scores. Design: Cross-sectional, correlational. Methods: Data were collected from male and female team- and individual-sport athletes and corporate- and bodybuilding-gym exercisers. Two samples ( n sample 1  = 318; n sample 2  = 300) were utilized in instrument development and score validation and another ( n sample 3  = 101) in examining test-retest reliability and stability of scores. Samples 1 and 2 responded to the newly developed items alongside others assessing theoretically-related variables, whereas Sample 3 completed the new instruments on two separate occasions. Results: Factor analyses identified the final items and dimensional structures for the Doping Moral Disengagement Scale (DMDS), Doping Moral Disengagement Scale–Short (DMDS–S) and Doping Self-Regulatory Efficacy Scale (DSRES). The DMDS has six lower- and one higher-order factor, whereas the DMDS-S and DSRES are unidimensional. These structures were invariant by sex and sport/exercise context. Evidence supporting external validity, test-retest reliability, and stability of scores was also provided. Conclusion: This research developed and provided evidence of score validity and internal consistency for three instruments relevant to doping in sport and exercise. Highlights: Measures of doping moral disengagement and self-regulatory efficacy were developed. A short and a long version of the doping moral disengagement measure was created. Good levels of internal consistency, test-retest reliability and stability were shown for all instrument scores. Evidence supporting the construct validity of all instrument scores was provided. Measurement invariance was also examined for gender and physical activity context.